Análise termoeconômica de uma planta rural de biogás integrada a um sistema de fertirrigação - Vaz, Victor (2022)
The segment of biofertilizers stabilized in anaerobic digesters presents itself as a promising solution in the correct structuring of Brazilian soils and in the reduction of dependence on imported products. And one of the great challenges for the development of this sector is the logistics, cost and feasibility of treatment, transport and distribution of such organic fertilizers. In this sense, this work proposes a study of the thermoeconomic feasibility of a biodigester coupled to a fertigation system, entitled "integrated system" and the Pastore plant, located in Toledo (PR). In this way, analyzes of the first and second laws of thermodynamics will be carried out, through the multiplication of the incidence matrices by the energy and exergy fluxes. In addition to economic evaluations of the implementation of the two proposed systems, such as the allocation of the costs of the generated products and analysis of economic viability. Some of the results indicated that the energy consumption to fertigate one m³ of swine manure, under the analyzed fertigation conditions, corresponds to only 1.55% of the electricity generation potential of these manure, estimated at 15.20 kWh/m³ and 19, 13 kWh/m³ in terms of energy and exergy, respectively, which would allow the energy self-sufficiency of the system. The economic indicators calculated from the revenues and costs of the products of the Pastore plant and the integrated system over 10 years, reveal that both are viable, with the integrated system being more attractive than the Pastore plant, with higher NPV and IRR. However, the profit from the sale of electricity generated in the biogas plant is higher than the cost avoided with the energy self-sufficiency of the fertigation systems, therefore, this is not the factor that would make the integrated system more financially attractive, but the sale of liquid biofertilizer.